Recurrence of an early postzygotic rescue of an inherited unbalanced translocation resulting in mosaic segmental uniparental isodisomy of chromosome 11q in siblings. Issue 10 (27th May 2021) - Blanluet, Maud; Chantot‐Bastaraud, Sandra; Chambon, Pascal; Cassinari, Kévin; Vera, Gabriella; Goldenberg, Alice; Keren, Boris; Le Meur, Nathalie; Hannequin, Didier; Mace, Bertrand; Siffroi, Jean‐Pierre; Frebourg, Thierry; et al.
Abstract: Balanced translocations are associated with a risk of transmission of unbalanced chromosomal rearrangements in the offspring. Such inherited chromosomal abnormalities are typically non‐mosaic as they are present in the germline. We report the recurrence in two siblings of a mosaicism for a chromosomal rearrangement inherited from their asymptomatic father who carried a balanced t(2;11)(q35;q25) translocation. Both siblings exhibited a similar phenotype including intellectual disability, dysmorphic features, kyphoscoliosis, and cervical spinal stenosis. Karyotyping, fluorescence in situ hybridization and SNP array analysis of blood lymphocytes of both siblings identified two cell lines: one carrying a 2q35q37.3 duplication and a 11q25qter deletion (~90% cells), and one carrying an 11q uniparental isodisomy of maternal origin (~10% cells). We hypothesize that these mosaics were related to a postzygotic rescue mechanism which unexpectedly recurred in both siblings.